Social, economic and cultural aspects of transportation accessibility in mountanious areas, on the example of Tatra County, Poland - Kretowicz, Paweł (Journal for Geography, 2008)
In this article, spatial variations both in local and regional transportation accessibility are looked at through the lenses of the social, economic and cultural environments of Tatra County. A number of methods are applied in the analysis of daily links, prices and travel time to the county capital. A comparison between local, private carriers and the National Bus Company (PKS) is made to illustrate the ongoing economic processes and their effects in this mountainous region. Also, a relationship between the Podhale, Spisz and Orawa social regions and transportation accessibility is presented as an example of certain cultural determinants of the latter. As such, this study contributes to the understanding of mobility problems in mountainous touristic areas.